Rhombencephalosynapsis in a severely polymalformed fetus with non-mosaic tetrasomy 9p, in intracytoplasmic-sperm-injection pregnancy - di Vera, Elena (Springer US, 2008)
CASE REPORT: A fetus with rhombencephalosynapsis and prenatally diagnosed tetrasomy 9p is reported. Chromosomal analysis from amniocyte culture revealed non-mosaic supernumerary chromosome identified as isochromosome 9p (9p24→q13::q13→p24). Ultrasound scan revealed intrauterine growth retardation, renal anomalies, cardiac anomalies, ventriculomegaly, and agenesis of cerebellar vermis with fusion of the cerebellar hemispheres. CONCLUSION: Although most cases of cerebellar vermis agenesis in tetrasomy 9p are described with cystic malformation such as Dandy-Walker anomaly, our case indicates that this chromosomal disorder should be taken into account in fetuses with the development of cystic and non-cystic malformations of cerebellar vermis and posterior fossa.